(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: Financial statements are essential tools used by businesses to evaluate their financial health and performance. This article explores the three primary financial statements: the income statement, the balance sheet, and the cash flow statement. The income statement provides insights into a company’s profitability over a specific period, outlining revenues and expenses. The balance sheet presents a snapshot of the company’s financial position, listing assets, liabilities, and equity at a given point in time. The cash flow statement tracks the movement of cash in and out of the business, highlighting operational, investing, and financing activities. Understanding these statements is crucial for business owners, investors, and stakeholders in making informed financial decisions.